Putative periodontal pathogens in the subgingival plaque of Sudanese subjects with aggressive periodontitis - Hashim, N.T.; Linden, G.J.; Winning, L.; Ibrahim, M.E.; Gismalla, B.G.; Lundy, F.T.; El Karim, I.A. (Archives of oral biology, 2017)
•The article describes the prevalence of putative periodontal pathogens in high-risk population for aggressive periodontitis (AgP) using qPCR.•The association of the bacteria with the cases of AgP depends on the detection threshold level.•Pathogen of the red complex particularly T. forsythia and T. denticola had a high prevalence (>70%) in AgP cases at all detection levels, whereas P. gingivalis was more prevalent at the lowest detection threshold.•Actinomycetemcomitans was identified less frequently than the other bacterial species with no difference in its prevalence between cases and controls. There has been limited study of the bacterial species associated with aggressive periodontitis (AgP) in high-risk populations in Africa. The aim of this study was to investigate and quantify the presence of four putative periodontal pathogens in the subgingival plaque of Sudanese subjects with AgP. A secondary aim was to investigate the effect of varying the detection threshold on the reported prevalence of the bacterial species investigated. Subgingival plaque samples were collected from AgP cases (n=73) and healthy controls (n=71). Bacterial DNA was extracted and analyzed by quantitative polymerase chain reaction for the detection and quantification of four putative periodontal pathogens: Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, Treponema denticola and Tannerella forsythia. At the lowest detection threshold (>101 cells), P. gingivalis (p<0.0001) was more prevalent in AgP cases than controls. T. forsythia and T. denticola had a high prevalence (>70%) in AgP cases at all detection levels. While T. forsythia was significantly more frequently identified in AgP than in controls at all detection thresholds, this was only the case for T. denticola at the intermediate threshold (>102 cells). A. actinomycetemcomitans was identified less frequently than the other bacterial species with no difference in its prevalence between AgP cases and controls. The prevalence of the putative periodontal pathogens investigated varied considerably in Sudanese subjects with AgP and in periodontally healthy controls depending on the detection thresholds applied. T. forsythia was identified as having the strongest association with AgP.